2022
DOI: 10.3390/ijerph19052935
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Variations of Well-Being and Interactions with Training and Match Intensities: A Descriptive Case Study in Youth Male Soccer Players

Abstract: The aim of this study was two-fold: (i) analyze the weekly variations of well-being and training/match intensity measures in youth soccer players, and (ii) test relations between well-being and training intensity outcomes. The study followed a descriptive case study design. Twenty-seven under-17 male soccer players were monitored for well-being and training intensity parameters over seventeen consecutive weeks. An adjusted version of the Hooper questionnaire was used to monitor the perceptive sleep quality, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 30 publications
3
16
1
Order By: Relevance
“…Indeed, form our findings, it seems that with lower mTI (mean of the intensity of all sessions and match), higher values of sleep quality (bad sleep quality) are perceived by players. This finding is in concordance with the findings of a very recent study that suggested that higher TI levels are associated with greater levels of readiness and sleep quality [ 20 ]. As sleep quality has an enormous and determinant impact on athletes’ performance [ 30 ], ensuring a cautious planning of the imposed weekly TI measures, namely, TM, and mTI measures, can potentially improve the players’ sleep quality and readiness to train [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Indeed, form our findings, it seems that with lower mTI (mean of the intensity of all sessions and match), higher values of sleep quality (bad sleep quality) are perceived by players. This finding is in concordance with the findings of a very recent study that suggested that higher TI levels are associated with greater levels of readiness and sleep quality [ 20 ]. As sleep quality has an enormous and determinant impact on athletes’ performance [ 30 ], ensuring a cautious planning of the imposed weekly TI measures, namely, TM, and mTI measures, can potentially improve the players’ sleep quality and readiness to train [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…The magnitude of the between-week differences found for well-being measures at the early- and in-season-periods were similar to those reported in a recent study conducted on 27 under-17 football players [ 20 ]. Specifically, that study [ 20 ] revealed similar magnitudes for fatigue ( p < 0.001; η2 = 0.147) and for DOMS ( p = 0.001; η2 = 0.127) but not for sleep quality ( p < 0.001; η2p = 0.140), which had a small magnitude compared to the trivial magnitude found in the present study. However, our study followed a different design, i.e., 38 weeks were analyzed, while the aforementioned study [ 20 ] analyzed only 17 weeks, corresponding to the pre- and early-season.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Despite the widespread use of player monitoring systems, and the promising prospects of using machine learning to predict player wellness, there is currently a gap in research linking perceived wellness factors to individual player performance. While studies have investigated connections between wellness factors and various measures such as injuries (Sioud et al, 2023), training load (Moalla et al, 2016), and rate of perceived exertion (Silva et al, 2022), there is limited evidence supporting a causality between wellness and individual player performance. Despite the consensus that maintaining balance in wellness and psychological well-being can enhance elite athlete performance (e.g., Giles et al, 2020;McGuigan et al, 2020), more research is needed to evaluate any causal relationship between perceived wellness and objective match performance at the individual level.…”
Section: Quantifying Athlete Wellness: Investigating the Predictive P...mentioning
confidence: 99%